Genomic Exploration of Nonalcoholic Fatty Liver Disease: Insights From Gene Expression and Variation in Morbidly Obese Individuals - Tamadher Abbas Rafaa; Safa Abbas Khudhair; Zahraa Yassen Mohammed; Ahmed AbdulJabbar Suleiman (Journal of Obesity)
Nonalcoholic fatty liver disease (NAFLD) is a common liver condition resulting from metabolic syndrome characterized by fat accumulation in the liver. It is often associated with obesity and diabetes, contributing to hepatic steatosis in liver cells. The prevalence of NAFLD is increasing globally, with 32% of the adult population affected. Genetic modifiers, such as single nucleotide polymorphisms, can increase susceptibility to the disease. Gene expression analysis and genetic variation can help identify disease-causing pathways and reveal biomarkers involved in NAFLD. This study employed integrative bioinformatics analysis, including bulk RNA-seq and single-cell RNA-seq, to explore differentially expressed genes and their genetic variants in NAFLD vs. control and NAFLD vs. cirrhosis, highlighting genes influencing NAFLD progression. Moreover, this study identified AKR1D1, LIPC, UGT2B17, DGAT2, and SERPINE1 implicated in metabolic, immune, and lipid functions while being overexpressed in both hepatocyte cells among obese patients identified and validated through Liver Cell Atlas, highlighting their pivotal role in the pathogenesis of the disease in obese patients through perturbed hepatocytes. Furthermore, novel pathogenic variants of AKR1D1, LIPC, and SERPINE1, associated with congenital bile acid synthesis defects, abnormal circulating lipid concentrations, and plasminogen activator inhibitor type 1 deficiency conditions, were identified. Conclusively, this integrative multiomics study highlights the novel pathogenic variants of AKR1D1, LIPC, and SERPINE1 in metabolic, immune, and lipid pathways that are highly expressed among hepatocytes in obese patients while possibly carrying pathogenic mutations that may be associated with NAFLD, emphasizing their potential as novel targets for therapeutic strategies and biomarker development in early diagnosis and treatment before the onset of cirrhosis or hepatocellular carcinoma.